Mean platelet volume provides beneficial diagnostic and prognostic information for patients with resectable gastric cancer - Shen, Xiao-Ming (Oncol Lett, 2016)
Gastric cancer is the fourth most frequent cancer and the second cause of cancer-related mortalities worldwide. Platelets play an important and multifaceted role in cancer progression. Elevated mean platelet volume (MPV) detected in peripheral blood has been identified in various types of cancer. In the present study, we investigated the application value of MPV in early diagnostic and prognostic prediction in patients with resectable gastric cancer. In total, 168 patients with resectable gastric cancer were included and separated into the gastric cancer and healthy control groups according to median pre-operatic MPV value (MPV low, <10.51 or MPV high, ≥10.51). The results showed that the pre-operatic MPV level was significantly higher in gastric cancer patients compared with the healthy subjects. Low pre-operatic MPV level correlated with improved clinicopathological features, including decreased depth of invasion, less lymphonodus metastasis and early tumor stage. The Kaplan-Meier plots showed that the patients with higher pre-operatic MPV had decreased overall survival (OS) and disease-free survival (DFS). Surgical tumor resection resulted in a significant decrease in the MPV level. The patients whose MPV level decreased following surgery had an improved OS. Multivariate Cox regression analysis revealed that the depth of invasion, lymphonodus metastasis, American Joint Committee on Cancer (AJCC) stage, and changes in MPV following surgery were prognostic factors affecting OS, and the AJCC stage and pre-operatic MPV were prognostic factors affecting DFS. In conclusion, MPV measurement can provide important diagnostic and prognostic results in patients with resectable gastric cancer.